PRESERVICE TEACHERS' INSTRUCTIONAL BELIEFS AND EXAMINATION OF CONSISTENCY BETWEEN BELIEFS AND PRACTICES - BEKİROĞLU, FERAL; AKKOÇ, HATİCE (SPRINGER, 2009)
The purposes of this study were to determine preservice physics teachers' instructional beliefs and to investigate the relationship between their beliefs and practices. The theoretical framework was based on the combination Haney & McArthur's (Science Education, 86(6):783-802, 2002) research and Ford's (1992) motivation systems theory. A multicase study design was utilized for the research in order to focus on a belief-practice relationship within several examples. Semistructured interviews, observations, and preservice teachers' written documents were used to collect data. Results showed that most preservice teachers held instructional beliefs aligned with constructivist philosophy. Some of the preservice teachers' beliefs were consistent with their practices while some of them presented different practices from their beliefs in different placements.
Keywords: classroom practice; constructivist teaching; instructional beliefs; preservice science teachers; pre-service teacher education; teacher belief; traditional teaching; PROFESSIONAL-DEVELOPMENT; SCIENCE-EDUCATION; ELEMENTARY-SCHOOL; IMPACT